THEORETICAL AND EPISTEMOLOGICAL DIMENSIONS OF INFORMATION LITERACY - Ernesto Manhique, Ilidio Lobato [UNESP]; Silva Casarin, Helen de Castro [UNESP] (Univ Federal Campina Grande, 2019)
This research aimed to identify the theoretical and epistemological dimensions of information literacy in sub-Saharan Africa. It adopted bibliographic research for theoretical construction about the subject and the collecting data was carried out through bibliographic survey in African Journals Online (AJOL), which is one of the biggest databases of scientific information in Africa. The results show that there is incipient integration of researches about this subject, whose theoretical underpinnings are influenced by standards and models produced in international level. There is no evidence that indicates that African researchers use local or national frameworks to underpin their researches and information practices. It concludes that there is a need of new approach that incorporates information practices based on local context, as a way to foment meaningful learning and critical consciousness.
Keywords: Information literacy; Epistemology; AJOL; Sub-Saharan Africa